(untitled) (Advancements in Homeopathic Research, 2025)
Introduction: IgA Nephropathy (IgAN) is the most prevalent form ofglomerulonephritis worldwide. Disease progression may lead to advanced chronic kidney disease (CKD) or end stage renal diseases (ESRD). Clinically, IgAN can remain asymptomatic or may present with persistent haematuria and proteinuria. Definitive diagnosis requires renal biopsy. Angiotensin-receptor blockers (ARBs) are commonly used to slow disease progression;however long-term use associated with potential adverse effects. Case summary: This case report presents a patient with symptoms including recurrent urinary tract infections (UTIs) menstrual irregularity, foamy and smoky coloured urine. Laboratory investigations revealed with elevated serum creatinine levels, and a renal biopsy confirmed a diagnosis of IgA nephropathy (IgAN) Thuja occidentalis and Eel serum were found effective in treatment of IgAN. Patients outcomes were assessed using validated tools including the impact outcome related to impact on daily living (ORIDL) and measure yourself medical outcome profile (MYMOP). To evaluate the causal relationship between the intervention and clinical outcomes the Modified Naranjo Criteria for Homoeopathy (MONARCH) inventory was employed. The findings suggest a potential therapeutic benefit of homoeopathic remedies as a part of integrative approach in the management of IgAN, meriting further systematic investigation through controlled clinical studies.